PELAKSANAAN PROGRAM BEDAH RUMAH DI DESA RANOKETANG ATAS, KECAMATAN TOULUAAN, KABUPATEN MINAHASA TENGGARA - SUMANGKUT, EUNIKE KEZIA; PANGKEY, MASJE; TAMPI, GUSTAAF (JURNAL ADMINISTRASI PUBLIK, 2021)
Self-Help Housing Stimulant Assistance (BSPS) or better known as Home Repair isone of the government programs to help people have a decent house as well as a means for social welfaredevelopment. This home renovation program has been implemented in many regions in Indonesia. Theaim of the researcher in conducting this research was to find out how the Home Improvement Programwas implemented in Ranoketang Atas Village. In this study, the researcher focused on the problems foundin the field, namely how the implementation of the Home Improvement Program in Ranoketang AtasVillage was in accordance with the factors that supported the implementation. According to Ksumanegara(2010), there are four factors that play an important role in the successful implementation of a policy.These factors are communication, resources, disposition, and bureaucratic structure. This study uses aqualitative method. Data is grouped to make it easier to filter which data is needed or not. After groupingthe data, the researcher describes it in text form, so that it is better understood, after that the writer drawsconclusions from the data so that it can answer the main problem of the research. The result of thisresearch is that the factors that play an important role in the successful achievement of a policy have beenfulfilled. Thus, the implementation of the house renovation program in Ranoketang Atas village has gonewell. This research is expected to provide benefits for the development of Social Sciences and can be usedas a reference for the Ranoketang Atas village government to maintain its performance in the houserenov.Keywords: Implementation, Program, Home Improvement, Communication, ation program and improvewhat is needed for the continuity of the program Resources, Disposition, Bureaucratic Structure.